Social Dynamics and Character Management in Jane Austen’s Pride and Prejudice: A Literary Analysis - Owot, Jennifer Akello (Journal of Educational Research and Policies, 2025)
The research paper examines Jane Austin’s Pride and Prejudice through the lens of marriage, Social Class, and Character development focusing on the evolving relationship between Darcy and Elizabeth Bennet. It explores how Austin critiques societal expectations of the 19th Century, particularly the interplay of wealth and romance, through key figures like Mr Collins and Mr Wickham. Drawing from textual the study highlights the novel’s enduring relevance in understanding human relationship culminating in a resolution that balances personal growth with societal norms.